Perceptions of the uses of routine general practice data beyond individual care in England: a qualitative study. Issue 1 (8th January 2018) - Wyatt, David; Cook, Jenny; McKevitt, Christopher
Abstract : Objective: To investigate how different lay and professional groups perceive and understand the use of routinely collected general practice patient data for research, public health, service evaluation and commissioning. Design, method, participants and setting: We conducted a multimethod, qualitative study. This entailed participant observation of the design and delivery of a series of deliberative engagement events about a local patient database made of routine primary care data. We also completed semistructured interviews with key professionals involved in the database. Qualitative data were thematically analysed. The research took place in an inner city borough in England. Results: Of the community groups who participated in the six engagement events (111 individual citizens), five were health focused. It was difficult to recruit other types of organisations. Participants supported the uses of the database, but it was unclear how well they understood its scope and purpose. They had concerns about transparency, security and the potential misuse of data. Overall, they were more focused on the need for immediate investment in primary care capacity than data infrastructures to improve future health. The 10 interviewed professionals identified the purpose of the database in different ways, according to their interests. They emphasised the promise of the database as a resource in health research in its own right and in linking it to other datasets. Conclusions: Findings demonstrate positivity to the uses of this local database, but a disconnect between the long-term purposes of the database and participants' short-term priorities for healthcare quality. Varying understandings of the database and the potential for it to be used in multiple different ways in the future cement a need for systematic and routine public engagement to develop and maintain public awareness. Problems recruiting community groups signal a need to consider how we engage wider audiences more effectively.